Knockdown of P2Y4 ameliorates sepsis-induced acute kidney injury in mice via inhibiting the activation of the NF-κB/MMP8 axis - Wang, Maojuan; Jiang, Fan; Zhang, Lian; Zhang, Juan; Xie, Hong (Frontiers in Physiology, 2022)
Sepsis-induced acute kidney injury (S-AKI) has emerged as a frequent and life-threatening complication in critically ill patients, which is characterized by a systematic inflammatory response and a rapid decline in kidney function. P2Y4, a member of G protein–coupled P2Y nucleotide receptor family, has been reported to serve as a crucial player in inflammatory responses during the development of neurocognitive disorder and myocardial infarction. Nonetheless, the biological role of P2Y4 in S-AKI remains largely unclear. This study aimed to decipher the biological role of P2Y4 in S-AKI and illuminate the potential mechanisms. In this study, S-AKI models were successfully established in mice via cecal ligation and puncture. Results showed that the kidney tissues from S-AKI mouse models exhibited a higher P2Y4 expression level than from the sham-operated group. Knockdown of P2Y4 was found to remarkably alleviate kidney damage and reduce inflammatory response in mice of S-AKI models. Moreover, P2Y4 ablation inhibited the activation of the NF-κB/MMP-8 signaling axis. Additionally, mechanistic studies revealed that rescuing MMP-8 reversed the alleviating effects of P2Y4 knockdown against renal cell damage. Collectively, our findings indicate that P2Y4 knockdown ameliorated S-AKI in mice via inhibiting the activation of the NF-κB/MMP-8 axis and that P2Y4 may represent a novel therapeutic target for S-AKI patients.